THE EFFECT OF LIQUIDITY AND CAPITAL STRUCTURE TO INCREASE FIRM VALUE THROUGH INCREASING FINANCIAL PERFORMANCE - Imronudin, I; Waskito, Jati; Cantika, Ikeke Bunga; Sofiardhani, Gramitha (Riset Akuntansi dan Keuangan Indonesia, 2022)
This study analyzes the effect of capital structure, liquidity, company growth, and size on firm value. This study uses financial performance as a mediating variable. The object of this study is Manufacturing Companies listed on the Indonesia Stock Exchange for the 2020 period. Using a purposive sampling technique, the sample in this study consisted of 150 companies. The data collected from the financial statements are then analyzed using multiple linear regression. The study results show that capital structure positively and significantly affects firm value. Likewise, financial performance shows a positive and significant influence on firm value. The capital structure negatively affects firms’ value. Liquidity variables, and company growth, partially do not affect firm value. When testing whether there is a mediating effect, it is found that financial performance cannot mediate the relationship between capital structure and firms’ value. Furthermore, financial performance can mediate the relationship between sales growth and firm value.